2010
DOI: 10.1111/j.1462-2920.2010.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Culturable Rhodobacter and Shewanella species are abundant in estuarine turbidity maxima of the Columbia River

Abstract: SummaryMeasurements of dissolved, ascorbate-reducible and total Mn by ICP-OES revealed significantly higher concentrations during estuarine turbidity maxima (ETM) events, compared with non-events in the Columbia River. Most probable number (MPN) counts of Mn-oxidizing or Mn-reducing heterotrophs were not statistically different from that of other heterotrophs (10 3 -10 4 cells ml −1 ) when grown in defined media, but counts of Mn oxidizers were significantly lower in nutrient-rich medium (13 cells ml −1 ). MPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 102 publications
(138 reference statements)
2
30
0
Order By: Relevance
“…While manganese reduction in the Shewanella genus has been investigated extensively, the possibility of manganese oxidation has not been investigated in any detail. However, Shewanella species have been found as part of manganese-oxidizing communities and were recognized as being important in manganese cycling in the Columbia River in the United States (46,47). Furthermore, Bräuer and colleagues (47) found that the manganese-oxidizing Shewanella isolates were most closely related to S. denitrificans, a moderate oxidizer in our studies.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…While manganese reduction in the Shewanella genus has been investigated extensively, the possibility of manganese oxidation has not been investigated in any detail. However, Shewanella species have been found as part of manganese-oxidizing communities and were recognized as being important in manganese cycling in the Columbia River in the United States (46,47). Furthermore, Bräuer and colleagues (47) found that the manganese-oxidizing Shewanella isolates were most closely related to S. denitrificans, a moderate oxidizer in our studies.…”
Section: Discussionsupporting
confidence: 48%
“…However, Shewanella species have been found as part of manganese-oxidizing communities and were recognized as being important in manganese cycling in the Columbia River in the United States (46,47). Furthermore, Bräuer and colleagues (47) found that the manganese-oxidizing Shewanella isolates were most closely related to S. denitrificans, a moderate oxidizer in our studies. Similarly, manganese-oxidizing Shewanella isolates were found as part of the microbial community at Vailulu'u Seamount, Samoa (48).…”
Section: Discussionsupporting
confidence: 48%
“…CMOP installed a flow-through system (with salinity, temperature, chlorophyll a, and turbidity sensors) and a downward looking ADP, which perform automated data collection during CCC classes, station deployments, and other periods of serendipity vessel operation. In addition, the M/V Forerunner is used by CMOP and other scientists for short-term field campaigns (Roegner et al, 2011a, b;Bräuer et al, 2011Bräuer et al, , 2013Peterson et al, 2013;Kahn et al, 2014) and calibration sampling near endurance stations.…”
Section: Pioneer Arraymentioning
confidence: 99%
“…Multiple UNOLS 1) research vessels -65 ft (20 m) R/V Clifford Barnes, 135 ft (41 m) R/V Point Sur, 143 ft (44 m) R/V Horizon, and 177 ft (53 m) R/V Wecoma and R/V Oceanus -have been used in CMOP campaigns across the river-to-shelf continuum (Smith et al, 2010(Smith et al, , 2012(Smith et al, , 2013Anderson et al, 2011;Bräuer et al, 2011, 1) The University-National Oceanographic Laboratory System (UNOLS) is an organization of U.S. academic institutions and national laboratories that provides access to research ships and other oceanographic research facilities. 2013; Fortunato and Crump, 2011;Herfort et al, 2011bHerfort et al, , 2012DeLorenzo et al, 2012;Fortunato et al, 2012Fortunato et al, , 2013Maier et al, 2012;Durkin et al, 2013;Evans et al, 2013;Gilbert et al, 2013;Peterson et al, 2013;Kahn et al, 2014).…”
Section: Pioneer Arraymentioning
confidence: 99%
“…Column "Processes" and "Environment" provide information about the major functions and processes as well as the environments in which the most predominant OTUs were encountered as predicted based on a literature review (column "References"). Hypersaline, saline and freshwater (Bräuer et al, 2011;Glöckner et al, 1999;Hiraishi et al, 1995;Kawasaki et al, 1993;Stapleton et al, 2000;Yang et al, 2012) (Besemer et al, 2012;Khemkhao et al, 2011;Kim et al, 2013;Qu and Yuan, 2008;Singleton et al, 2011;Torrentó et al, 2011) 3 71 The role of environmental microbiota Fish live and share their environment with microorganisms. The autochthonous microbiota of fish mostly originates from those present in their feed and water.…”
Section: Resultsmentioning
confidence: 99%